A 10-week randomized trial comparing eccentric vs. concentric hamstring strength training in well-trained soccer players - Mjolsnes, R.; Arnason, A.; Osthagen, T.; Raastad, T.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2004)
Purpose: To compare the effects of a 10-week training program with two different exercises traditional hamstring curl (HC) and Nordic hamstrings (NH), a partner exercise focusing the eccentric phase on muscle strength among male soccer players. Methods: Subjects were 21 well-trained players who were randomized to NH training (n=11) or HC training (n=10). The programs were similar, with a gradual increase in the number of repetitions from two sets of six reps to three sets of eight to 12 reps over 4 weeks, and then increasing load during the final 6 weeks of training. Strength was measured as maximal torque on a Cybex dynamometer before and after the training period. Results: In the NH group, there was an 11% increase in eccentric hamstring torque measured at 60° s1, as well as a 7% increase in isometric hamstring strength at 90°, 60° and 30° of knee flexion. Since there was no effect on concentric quadriceps strength, there was a significant increase in the hamstrings:quadriceps ratio from 0.89±0.12 to 0.98±0.17 (11%) in the NH group. No changes were observed in the HC group. Conclusion: NH training for 10 weeks more effectively develops maximal eccentric hamstring strength in well-trained soccer players than a comparable program based on traditional HC.